Indigenous peoples images: from the 19th century's photographs to Claudia Andujar's photographs: Indigenous peoples images: from the 19th century's photographs to Claudia Andujar's photographs (Revista de História da UEG (REVHIST), 2020)
This article aims to analyze the way Cláudia Andujar's photos break with a certain image and discursive repertoire consolidated over the 19th and 20th centuries about the representation of indigenous peoples. The construction of a discourse on indigenous peoples in the 19th century is analyzed through the photographic production of missionaries who participated in expeditions organized to explore Brazilian territory. Regarding the photographic production of the 20th century, the investigation starts from the images produced by the Rondon Commission and by the photo reports from the magazine O Cruzeiro. In 1970, Claudia Andujar starts to introduce an innovative way of producing these photographs: result of a long relationship of affection and engagement with the Yanomami, her work combines the aesthetics of images with an attempt to translate the shamanic experience, central to the existence of the Yanomami people.Keywords: Photography. Claudia Andujar. Yanomami. Indigenous peoples.